COVID-19 as a tourist activity inhibitor as evidenced by Poles’ holiday plans - Klaudyna Kowalska; Agnieszka Niezgoda (Studia Periegetica, 2020)
As a result of the global COVID-19 pandemic, we are facing challenges of the social and economic crisis. Its effects are difficult to estimate, but the impact on the tourism industry is undeniable. This is also true of the behavior of consumers of tourism services, whose attitudes towards travel are likely to change radically. The aim of the study presented in this article is to determine how Polish tourists have changed their travel plans and the way they organize their travels during and after the COVID-19 pandemic. The authors argue that the pandemic is an inhibitor of tourist activity. Data for the study were collected using an online pilot survey of 190 Polish adults. The first part of the questionnaire included general demographic questions about the respondents. The main part was divided into three sections related to COVID-19 and regarding: 1) changes in their occupational status and financial well-being, 2) their travel plans, and 3) their willingness to use peer-to-peer accommodation (e.g. Airbnb). The results show that the pandemic is not only an inhibitor of tourist activity, but can also trigger the substitution effect in the tourism market. Potential tourists can choose not to buy tourism services and instead spend their money on other forms of leisure (“external” substitution outside the tourist market) or can choose a more competitively priced tourism service (“internal” substitution). The COVID-19 pandemic has negatively affected the financial well-being and occupational status of some respondents and the vast majority of respondents have had to modify or cancel their holiday plans. While the pandemic may help to stimulate domestic tourism, the preference for self-organized holiday trips, expressed by the respondents, herald further problems of tour operators. Although the financial well-being of many respondents has deteriorated, the number of those interested in cheaper accommodation for future trips was much smaller compared to those who reported such a preference before the pandemic.